Cooling Out Undergraduates with Health Impairments: The Freshman Experience. (1st November 2016) - Carroll, Jamie M.; Muller, Chandra; Pattison, Evangeleen
Abstract : Students with health impairments represent a growing sector of the college population, but health-based disparities in bachelor's degree completion persist. The classes students pass and the grades they receive during the first year of college provide signals of degree progress and academic fit that shape educational expectations, potentially subjecting students to a cooling out process (Clark, 1960). Using the Beginning Postsecondary Students Longitudinal Study (BPS 04/09), we compared signals of degree progress and academic fit and changes in educational expectations between students with and without health impairments during the first year of college. We found that net of academic preparation, type of institution, enrollment intensity and first year experiences, students with mental impairments were more likely to lower their educational expectations after the first year of college, due partially to negative signals of academic fit. We found limited evidence that gaps in learning are related to the use of academic accommodations for students with health impairments. Our results suggest that students with mental impairments are disadvantaged in reaching first year benchmarks of degree progress and academic fit and are disproportionately cooled out.